2022
DOI: 10.1021/acssuschemeng.2c03915
|View full text |Cite
|
Sign up to set email alerts
|

Role of Binder in Cu2O Gas Diffusion Electrodes for CO2 Reduction to C2+ Products

Abstract: The electrochemical CO 2 reduction reaction (CO 2 RR) to form C 2+ products was investigated to obtain high selectivity in liquid CO 2 -fed systems having the limitation of low current density. Over the past decade, flow cells with gas diffusion electrodes (GDEs) have emerged to achieve high current densities close to the industrial-relevance scale by overcoming gas diffusion limitations. However, key parameters of GDE design, including binders, were not sufficiently identified to enhance selectivity and curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…After all, to accurately produce the required product, it is essential to conduct research that considers the material and type of the substrate, the type of the binder, the type of the reactor, the operating conditions of the reactor, and the supply type of the reactant. [140][141][142] The reaction pathway for a specific C 2+ product must be manipulated by controlling the above properties. However, the complex reaction mechanism of the CO 2 ECRR has not been identified because of insufficient reaction intermediate products after the formation of CC coupling (*CO*CHO intermediate).…”
Section: Discussionmentioning
confidence: 99%
“…After all, to accurately produce the required product, it is essential to conduct research that considers the material and type of the substrate, the type of the binder, the type of the reactor, the operating conditions of the reactor, and the supply type of the reactant. [140][141][142] The reaction pathway for a specific C 2+ product must be manipulated by controlling the above properties. However, the complex reaction mechanism of the CO 2 ECRR has not been identified because of insufficient reaction intermediate products after the formation of CC coupling (*CO*CHO intermediate).…”
Section: Discussionmentioning
confidence: 99%
“…As *CO adsorption energy in Cu-based catalysts is monotonically increased with the copper oxidation state, Cu 2+ species can be directly designed as catalysts to advance the C–C coupling toward C 2 product generation. However, Cu 2+ species may be reduced to Cu 0 under CO 2 ER conditions, leading to the degradation of activity and durability of CO 2 ER. , Heteroatom doping can introduce new active sites and protect the valence states of Cu species through energy level hybridization with the d-band center of the original Cu-based catalyst, modulating the adsorption behaviors of the intermediates and directing the CO 2 ER pathway toward a desired C 2 product. ,, Therefore, constructing the CuO nanostructure by Ce doping can be expected to regulate the adsorption strengths of the intermediates for maneuvering C–C coupling and the hydrogenation process toward the conversion of CO 2 ER to C 2 H 6 . Recently, a gas diffusion electrode (GDE)-equipped flow-cell electrolyzer has been engineered for CO 2 ER to the desired products at commercially relevant current densities by circumventing the mass transport limitation of CO 2 , , where the gas diffusion electrode (GDE) in a flow cell should be highly hydrophobic and porous to promote CO 2 diffusion and prevent flooding. , In this study, Ce 4+ -doped CuO mesoporous nanosheets are designed for CO 2 ER to C 2 H 6 in a flow cell. Ce 4+ doping induces oxygen vacancies and modulates the electron distribution of CuO, which increases the electron density of Cu sites near Ce 4+ sites and oxygen vacancies, ensuring adequate coverage of a *CO intermediate to promote C–C coupling, while the electron-deficient Cu sites away from Ce 4+ sites and oxygen vacancies strengthen the interaction with the CH 3 CH 2 O* intermediate, favoring its further conversion to C 2 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Their study revealed that an increase in the potentials and phosphate ion concentration promoted the branched-3D growth which gave maximum efficiency towards ECO 2 R. 35 Moreover, the choice of the surface chosen for electrodeposition is also an important factor that can determine the size, structure and morphology of the deposited material for electrocatalytic applications. 23,35,40 So far, many electrodeposited materials on the surfaces of Cu foil, Cu disc, PANI, Toray sheets with a gas diffusion electrode, Ni-foam and FTO 33,[41][42][43][44][45] have been reported for the application of ECO 2 R, but electrodeposition of nanostructured Cu 2 O on stainless steel (SS-316) has not been explored for ECO 2 R, even though a copper layer can be deposited rmly on SS-316. Stainless steel is known to be stable, durable, less corrosive and a good electrical conductor which can be used as an electrode and current collector in electrochemical energy storage and conversion systems.…”
Section: Introductionmentioning
confidence: 99%